Controllable and stable organometallic redox mediators for lithium oxygen batteries. Issue 1 (4th September 2019) - Kwak, Won-Jin; Mahammed, Atif; Kim, Hun; Nguyen, Trung Thien; Gross, Zeev; Aurbach, Doron; Sun, Yang-Kook
Abstract : We introduce corrole-chelated metal complexes as stable redox mediators with adjustable redox potential in lithium–oxygen batteries. Abstract : The use of electrocatalysis in lithium–oxygen batteries is mandatory for reducing the over-potentials of the oxygen evolution reaction (OER), below the levels that endanger the anodic stability of the electrolyte solutions and the carbon electrodes. The most effective catalysts for the OER are solubilized redox mediators that may be oxidized at relatively low potentials, but still capable of oxidizing Li2 O2 back to molecular oxygen. Since for the effective and long-term utilization of redox mediators in lithium–oxygen cells a clear evaluation of their stability is essential, we have developed a useful methodology for that purpose. This revealed, quite surprisingly, that most commonly used redox mediators are unstable in lithium–oxygen cells, even under argon atmosphere and without being in contact with Li anodes. Using the abovementioned methodology for evaluating efficiency, we now introduce corrole-chelated metal complexes as stable redox mediators in lithium oxygen batteries. This was achieved by taking advantage of the facile methods for introducing changes in the corrole ligands and by choosing properly the central transition metal cation, two aspects that allow for adjusting the redox properties of the metal complexes for the operative voltage window. We outline further directions and believe that this work will promote optimized selection of redox mediators for lithium–oxygen batteries.